Blue Jean [videorecording (DVD)] - Oakley, Georgia; McEwen, Rosy; Hayes, Kerrie, 1986-; Halliday, Lucy; Page, Lydia; Booth-Steel, Amy; Cave, Farrah (Magnolia Home Entertainment, 2023)
"It's 1988 in England and a new law stigmatizing gays and lesbians forces Jean, a closeted gym teacher, to live a double life. As pressure mounts from all sides, the arrival of a new student catalyzes a crisis that will push Jean to the edge."--Container.